Morphological parameters of spleen and thymus of the male rats on the basis of the hirudological influence of Hirudo verbana - Aminov, R.; Aminova, A.; Makyeyeva, L. V.; Макєєва, Людмила Валеріївна (My University, 2022)
The aim of this work is to study the morphological parameters of the spleen and thymus of rats along with hirudological influence from Hirudo verbana. The work was carried out on 40 male outbred laboratory rats weighing 280–300 grams, age 6.5–7 months. Animals that had passed the quarantine regime and had no external manifestations of the disease were used for the study. Manipulations with animals were performed in compliance with regulated norms and rules for the treatment of laboratory animals. For the study, two groups of animals were formed – control and experimental. After fixation of rats, the medical leech Hirudo verbana with an average weight of 0.8 ± 0.1 g was put on the animals of experimental group. The place of setting is the coccyges zone. Four times with an interval of one time per week. Then the animals were decapitated and the spleen and thymus were removed for histological examination. The white pulp of the spleen was analyzed – the area and diameter of the lymphoid follicles and central arteries, the number of lymphocytes per unit area (400 μm2) in the lymphoid follicles, in the thymus – the number of cells per unit area, both in the cortex and in the medulla. Under the influence of biologically active substances of the medicinal leech in the white pulp of the spleen, the size of the lymphoid follicles and central arteries increases, the number of lymphocytes per unit area (400 μm2) of the lymphoid follicle increases, and in the thymus, both in the cortex and in the medulla, the number of cells increases per unit area (400 μm2), the predominance of the cortical over the medullar ones. As a result of the obtained experimental study, we revealed the immune stimulating effect of Hirudo verbana on the organs of the immune system of laboratory rats: thymus and spleen.
Keywords: medicinal leech; hirudological influence; morphogenesis; spleen; thymus